Idiopathic recurrent acute pancreatitis. (October 2018) - Guda, Nalini M; Trikudanathan, Guru; Freeman, Martin L
Summary: Idiopathic recurrent acute pancreatitis is clinically challenging and has substantial socioeconomic consequences. Investigations are expensive and often reveal little about the cause of the disease. Little is known about the interaction between genetic, environmental, anatomical, and other factors that contribute to the disease. Data on the efficacy, safety, and long-term outcomes of endoscopic therapies are scarce. The effect of idiopathic recurrent pancreatitis on quality of life is often underestimated. A more thorough examination of the causes of the disease and the roles of other associated risk factors is needed, as are well designed clinical studies with robust and objectively measurable outcomes. Ideally, evaluation of the causes of disease and therapy should be done only in specialised centres, should follow a protocol, and all outcomes should be formally assessed.